2007
DOI: 10.1017/s0021859607007447
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and quality of wheat under increased ultraviolet radiation (UV-B) at later stages of the crop cycle

Abstract: SUMMARYThe increase of ultraviolet (UV-B) radiation could be a challenge for wheat production systems in Southern Chile, as in other areas. Previous reports have shown that increased UV-B radiation decreases wheat yield by affecting both grain number and grain weight. However, contrasting results have also been published showing no effect on wheat biomass and grain yield. In addition, little is known about the effect of higher UV-B radiation at particular periods of the crop cycle on grain quality traits. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Literature research revealed that applied doses of UV-B radiation vary widely, both in terms of daily dose applied (e.g. 12, 13·3, 24, 49, 2·6 or 4·9 kJ/m 2 ) and duration of radiation treatment in general, ranging from 4 days to 12 weeks (Burchard et al 2000; Hofmann et al 2000; Nogues & Baker 2000; Alexieva et al 2001; Skórska & Szwarc 2007; Calderini et al 2008; Majer & Hideg 2012). The UV-B radiation reaching the earth's surface is much smaller than UV-A due to atmospheric depletion, but in the shorter wavelength of the UV-B region many biological responses are far greater (Madronich et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Literature research revealed that applied doses of UV-B radiation vary widely, both in terms of daily dose applied (e.g. 12, 13·3, 24, 49, 2·6 or 4·9 kJ/m 2 ) and duration of radiation treatment in general, ranging from 4 days to 12 weeks (Burchard et al 2000; Hofmann et al 2000; Nogues & Baker 2000; Alexieva et al 2001; Skórska & Szwarc 2007; Calderini et al 2008; Majer & Hideg 2012). The UV-B radiation reaching the earth's surface is much smaller than UV-A due to atmospheric depletion, but in the shorter wavelength of the UV-B region many biological responses are far greater (Madronich et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Each data point is mean of four replications and standard errors are shown if the values are larger than the symbols. have affected both uptake and translocation of nutrients as reported in other studies under UV-B treatments in soybean and other plants under UV-B radiation[25] [48][49].…”
mentioning
confidence: 87%
“…Moreover, UVB radiation decreased the area of the flag leaf (Li et al., 2000a) which contributes to grain filling for about 75% (Miller, ). Moreover, sensitivity to UVB radiation varies both between and within plant species (Hidema and Kumagai, ) and depends on plant developmental stage and experimental conditions as reported (Al‐Oudat, Baydoun, & Mohammad, ; Calderini, Lizana, Hess, Jobet, & Zuniga, ; Lizana, Hess, & Calderinni, ).…”
Section: Introductionmentioning
confidence: 92%
“…However, due to particular genotype‐specific responses, the effects of UVB radiation on wheat are still under discussion (Kakani et al., ; Kataria & Guruprasad, 2012a). Further, the majority of studies considered the effect of enhanced UVB radiation with lamp supplementation (Calderini et al., ; Li, Lilian, & Yanqun, ; Li et al., 2000a; Lizana et al., ; Yao, Chu, He, & Si, ; Zu, Li, Chen, & Chen, ), thus providing unnatural spectral radiation balance that can lead to unrealistic conclusions. On the contrary, only a few studies have been conducted for determining the effects of ambient UV (280–400 nm) radiation on wheat responses in terms of growth and yield by the exclusion of solar UV components (Flint & Caldwell, ; Kataria & Guruprasad, 2012a; Pal, Zaidi, Voleti, & Raj, ).…”
Section: Introductionmentioning
confidence: 99%